2006
DOI: 10.1167/iovs.05-0783
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of OCT Characteristics in Patients with Achromatopsia and Blue-Cone Monochromatism

Abstract: Quantitative OCT image analysis reveals distinct patterns for controls subjects and patients with ACH and BCM, respectively. Quantitative analysis of OCT imaging can be useful in differentiating retinal diseases affecting photoreceptors. Foveal thickness is similar in both normal subjects and patients with ACH but is decreased in patients with BCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
42
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 34 publications
3
42
1
Order By: Relevance
“…Intra-retinal thickness measurements were obtained using reflectivity profiles as described elsewhere. 15 The thickness measurements derived from both eyes were averaged and subsequently analysed similar to a one-eye study design as described by Ray et al 16 Grading foveal hypoplasia…”
Section: Optical Coherence Tomography Image Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intra-retinal thickness measurements were obtained using reflectivity profiles as described elsewhere. 15 The thickness measurements derived from both eyes were averaged and subsequently analysed similar to a one-eye study design as described by Ray et al 16 Grading foveal hypoplasia…”
Section: Optical Coherence Tomography Image Acquisitionmentioning
confidence: 99%
“…Intra-retinal thickness measurements were obtained using reflectivity profiles as described elsewhere. 15 The thickness measurements derived from both eyes were averaged and subsequently analysed similar to a one-eye study design as described by Ray et al 16 Grading foveal hypoplasiaThe rationale behind the grading system we adopted was based on the unique developmental processes occurring at the fovea (figure 1). During development of the fovea there is (i) centrifugal displacement of cells of the inner retina towards the periphery, (ii) centripetal migration of cone photoreceptors towards the location of the incipient fovea and (iii) cone specialization of the foveolar cones.…”
mentioning
confidence: 99%
“…1) results in a curve (light reflectivity profile [LRP]) with six distinct peaks, hereafter referred to as P1 to P6. 10,11 Compared with retinal anatomy, 12 these peaks represent the retinal pigment epithelium (P1), a highly reflective layer between inner and outer segments of photoreceptors (P2), the external limiting membrane (P3), the outer plexiform layer (P4), the inner plexiform layer, (P5) and the nerve-fiber layer/vitreoretinal interface (P6). It has been suggested that P2 arises from tightly packed mitochondria in the ellipsoid region of the photoreceptors.…”
mentioning
confidence: 99%
“…It has been suggested that P2 arises from tightly packed mitochondria in the ellipsoid region of the photoreceptors. 10 Because of its unique anatomy, the fovea lacks P4 and P5. The visibility of these peaks is crucial for image interpretation.…”
mentioning
confidence: 99%
See 1 more Smart Citation